Real estate investing 2025 - Tyson, Eric (Eric Kevin); Griswold, Robert (--For dummies., 2025)
"Real estate is always on the radar of investors looking for growth opportunities. Real Estate Investing For Dummies is your no-nonsense guide to adding real estate to your own portfolio. Considered one of the most desirable investment types, real estate is a great way to build wealth--if you know how to navigate the challenges. This book teaches you how to enhance your income by buying investment properties. It includes help with building a plan for raising capital, finding properties with promise, and becoming a successful property manager. With tips on increasing property value and creating a real estate portfolio that matches your goals, this guide is a must for any would-be real-estate investor."--Publisher's website.